Midlife creativity and identity : life into art - Miles, Philip (Bingley, U.K. : Emerald Publishing Limited, 2018)
Where does 'art' come from, and what is the 'meaning' of creativity? What inspires an artist in the middle phase of life and what value is placed on the pursuit of originality? Where do innovative ideas come from and how do they transmogrify into songs, art and stories? These are some of the questions posed in this ethnographic study, undertaken over three years and involving male and female musicians, artists and literary authors in the UK, some amateur and some professional but all dedicated to the invention of artistic legacy. This book sets out to understand the influences, spaces and routines of creative people experiencing midlife via an evocative exploration of biography, self-identity, inspiration, sociality, beliefs, emotion, career trajectory and life choices, and considered via in-situ observations of rehearsal, performance, exhibition, environment and working philosophy that contribute to the meaningful creation of novelty. While life experiences influence both the chosen and developed techniques of creating art and the art itself, artistic virtuosity is also arguably a conscious resistance to the banal securities of midlife in an age of inherent, perceived insecurity. Processes of creation, spaces of inspiration and the individualised value placed on artistic endeavour in uncertain times and at an uncertain time in life are understood via an original theory of the 'mezzanine', a sought-after in-between zone that abandons the ordinary and embraces an almost anarchic uncertainty where the promise of possibility and the pursuit of the delight of innovation provide an antidote to the banal 'everyday' and the routine expectancies of middle age.
Prelims -- Introduction: Life into Art -- Transformations -- Music, Midlife and Authenticity -- Lost in Space: Music and Aura -- Music, Sociality and Identity -- Art and Identity -- The Subterranean River -- Down in the Woods -- Inspiration by the Sea -- Literary Midlife Solitude Sitting -- Living a Dream and Dreaming a Living -- Shifting Rhythms and a Sense of Purpose -- Philip Miles (pp. 129 - 144) -- The Mezzanine and Midlife Creativity -- Afterword: Monday Afternoon and the Millennium -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Creative ability; Creation (Literary, artistic, etc.); Midlife crisis; Social Science -- Sociology -- General; Social & cultural anthropology, ethnography